Animation Videos Development Based on Realistic Mathematics Education to Improve III Grade Fraction Problem-Solving Skills - Dewantari, Sherly Agustina; Didith Pramunditya Ambara (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study addresses issues related to mathematics learning, particularly on the topic of fractions, which can enhance students' understanding and interest in mathematics learning. The study aims to develop the design and development of an Animation Video product based on Realistic Mathematics Education (RME), evaluate the quality of the Animation Video through expert evaluations, individual tests, and small group tests, and determine the effectiveness of the RME-based Animation Video media. The research follows the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation), with data collected through interviews, questionnaires, and tests. The data analysis techniques used are quantitative descriptive analysis and inferential statistics.The results of the study show that the RME-based Animation Video, developed using Canva and Camtasia, can be accessed via YouTube/Google Drive links. Expert evaluations yielded scores of 94.64% for content experts, 92.5% for instructional design experts, and 96.15% for media experts. Individual testing with three students yielded a score of 91.66%, while small group testing involving nine students resulted in a score of 92.22%, both of which are categorized as excellent. The t-test results show a value of 27.277, which is higher than the t-table value of 2.056 at a 5% significance level with 26 degrees of freedom, thus rejecting H0 and accepting H1, indicating that the average post-test score of students is higher than the average pre-test score. This study demonstrates that the RME-based Animation Video can improve students' understanding of the topic of fractions by making abstract concepts easier to grasp. This approach can enhance problem-solving skills and motivate students, making it a valuable tool for teachers and curriculum developers. Future research may explore its impact on other mathematics topics and at different grade levels.